Physiotherapy student interaction with home-based carers and the impact on service delivery - Rustin, Letitia (Division of Physiotherapy, 2015)
Introduction: The national health system is experiencing major challenges due to a shortage of key human resources and a quadruple burden of disease. A cadre of trained community health workers, namely home-based carers (HBCs), have been trained in response to an increased need for health services. It is unclear to what extent the HBCs are able to provide rehabilitation support to their clients. Methodology: A quasi-experimental design was used to identify the impact of the collaboration between HBCs and physiotherapy students. Fifty HBCs from four organisations working within the Cape Town Metropolitan area were randomly selected and assigned to a control (n=25) and experimental (n=25) group. A validated checklist, based on the National Guidelines on Home Based Care and Community Based Care (Department of Health. 2001), and a self-developed questionnaire was used to determine the demographics and training of the HBCs; and the conditions of their clients. Results: The results indicated that the HBCs were predominantly middle-aged females with a highest qualification of Grade 12. No differences in gender or age were seen when we compared the control and experimental groups. The mean age of our sample size was 40.9 years (SD 11.13 and range 20-67 years), with a mean age of 43.6 year (SD 10.7) in the control group; and 38.1 years (SD 11.1) in the experimental group. There was a significant difference in the mean career length (with a mean of 778 months in the control group, and 497 months in the experimental group (p=0.006)) and length of training (mean control group = 773 months and experimental group = 502 months (p=0.007)) between the control and experimental groups. Although the control group spent more time on wound care and mathematics, the content of training was similar across the four organisations with HIV/AIDS topics reported by all respondents. There were no differences between the groups with regards to client profile, which included age, diagnosis and main problems. Despite the similar training opportunities, the HBCs who hosted physiotherapy students demonstrated significantly more interventions in every domain (activities of daily living (p=0.025), personal needs (p=0.006), environment needs (p=0.002) and lifestyle needs (p<.001)) than those who had not been exposed to students, except for the Core Home/Community Based Care (CHBC) (p=0.743). From the 25 HBC's in the experimental group, only twenty completed the questionnaire with regards to attitude towards collaboration with students. Of these twenty, 16 indicated that they strongly agreed that working with physiotherapy students was a good experience and that the students contributed to their understanding of the clients and their conditions. Eighteen of them also indicated that they learned from the students. The students were also supportive towards this program as they responded positively on each question, except for learning from the HBCs, which had a high neutral response rate. Conclusion: The training of the HBCs seems to prepare them insufficiently towards the management of their clients, who present more often with chronic diseases of lifestyle than with communicable diseases, as seen in the past. Exposure to a different discipline within the home context does result in an improvement of skills, especially in areas not covered by basic training. HBCs' skills with regards to rehabilitation can be improved by collaboration with physiotherapy students at community placements. This collaboration is shown to be mutually beneficial. Therefore, we recommend the implementation of this collaboration model in future, as all health professionals need continuous support to maintain a high standard of care and upgrade their skills.